2020
DOI: 10.1007/s11164-020-04098-8
|View full text |Cite
|
Sign up to set email alerts
|

Methylation of 2-methylnaphthalene over metal-impregnated mesoporous MCM-41 for the synthesis of 2,6-triad dimethylnaphthalene isomers

Abstract: 2,6-dimethyl naphthalene (2,6-DMN) is one of the key intermediates for the production of polyethylene naphthalate (PEN), which demonstrates superior properties compared with the Polyethylene terephthalate (PET). However, the complex synthesis procedure of 2,6-DMN increases the production cost and decrease the comorcelisation of PEN. In this study, selective synthesis of 2,6-triad DMN isomers (1,5-DMN, 1,6-DMN and 2,6-DMN) have been investigated by the methylation of 2-methylnaphthalene (2-MN) over mesoporous C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 52 publications
(81 reference statements)
0
4
0
Order By: Relevance
“…Aside from the specifically targeted product 2,6-DMN in the methylation of NA, the products 1,5-DMN and 1,6-DMN are also regarded as valuable because they could both be readily converted to 2,6-DMN through isomerization. ,, As a result, the sum of the selectivities on 1,5-, 1,6-, and 2,6-DMNs (marked as 2,6-traid DMN) is considered in place of the selectivity of 2,6-DMN to evaluate these catalysts. This approach provides insight into the indirect selectivity of 2,6-DMN …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Aside from the specifically targeted product 2,6-DMN in the methylation of NA, the products 1,5-DMN and 1,6-DMN are also regarded as valuable because they could both be readily converted to 2,6-DMN through isomerization. ,, As a result, the sum of the selectivities on 1,5-, 1,6-, and 2,6-DMNs (marked as 2,6-traid DMN) is considered in place of the selectivity of 2,6-DMN to evaluate these catalysts. This approach provides insight into the indirect selectivity of 2,6-DMN …”
Section: Resultsmentioning
confidence: 99%
“…Based on the aims of achieving catalysts with relatively high catalytic activity, convenient preparation, and environmental friendliness, we reported the methylation of NA over a series of Al-modified SiO 2 catalysts synthesized by a hydrothermal method for the preparation of 2,6-triad DMN (the sum of 2,6-DMN, 1,6-DMN, and 1,5-DMN). , Research has found that the Al content is related to the Brønsted/Lewis acid ratio, the amount of acid, and the acid strength. It has been shown that carbon accumulation occurs at strong acid sites over the zeolite catalysts, and then coke deposition rapidly leads to catalyst deactivation .…”
Section: Introductionmentioning
confidence: 99%
“… 58 For Cu/MCM-41 the strong peaks (2 θ ) at 43.9°, and 45.5° are attributed to the (1 1 0), (2 0 0), and (2 2 0) planes. 59 For Cu/Al 2 O 3 the diffraction peaks of the samples correspond to the characteristic face centered cubic (FCC) copper lines indexed as (1 1 1), (0 0 2) and (0 2 2) that were observed in these samples at diffraction angles of 43.2°, 50.3° and 73.9°, respectively (JCPDS No. 98-000-9057).…”
Section: Resultsmentioning
confidence: 99%
“…The FTIR results show similar characterisitc peaks for all samples, but the intensity of the peaks varies (Figure 1). The wide band from 3100 to 3600 cm −1 was associated with the hydrogen-bonded hydroxyl group in addition to the potential overlapping of -NH with -OH bonds (Figure 1) [74,75]. This band is potentially due to symmetric and asymmetric stretching vibrations of H 2 O molecules [76,77] and/or non-bounded -OH groups such as alcohols, carboxylic acid, and/or phenolic compounds [78,79].…”
Section: Characterisation Of Biosorbentsmentioning
confidence: 99%